Tamarind Kernel Powder (Tamarindus Indica) Processing (Reviews on Roasting Temperature and Roasting Duration - Pulungan, M. Hindun; Sukardi, Sukardi; Maryani, E. F. Sri; Atifah, Nur; Sucipto, Sucipto (Jurnal Teknologi Pertanian, 2001)
Tamarind kernel is a kind of waste that is not yet used optimally. As natural hydrocolloid source, for it is containing starch and gum, the kernel can be changed in powder form to increase its utility. In powder processing, kernel shell must be separated. One manner to separate it is by roasting where problem of roasting Research is designated to achieve combination of the best behavior of roasting temperature and roasting duration in processing of tamarind kernel as well as the calculation of production cost. Hypothesis is made. It is estimated that the inter-relation between roasting temperature and roasting duration increases the characters of tamarind kernel powder. Experimental method is used. Group random engineering, arranged by factorial, that is, two factors and three replications is implemented. Factor I is roasting temperature such as 1400C, 1500C, 1600C, and Factor II is roasting duration such as 10 minutes, 15 minutes, and 20 minutes. Analysis result of product random on tamarind kernel powder indicates that interaction between roasting temperature and roasting duration on water level, powder degree, viscosity, gel strength, rendemens and color pleasure is observed. However, interaction between roasting temperature and roasting duration in scent pleasure is not achieved. Analysis to obtain the best alternative results in best alternative of roasting temperature treatment at 1400C for 10 minutes by water level averages to 8,717% bk, starch level to 61,18% bk, viscosity 53,82 cP, gel strength 0,0097 mm/g/seconds, color and scent pleasures and rendements to 77,17% bk, production cost in first year is Rp. 525,00 for each 1 kg. Â  Keywords: tamarind kernel, roasting